Routing Selection Policy on Mobile Ad-Hoc Network using Trust based Mechanism Through AODV Routing Protocol - Matre , Versha; Vikhar , Pradnya A. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This research article provides a detailed examination of a new Trust-Aware On-Demand Distance Vector (Proposed_TAODV) protocol specifically developed for Mobile Ad Hoc Networks (MANETs). It evaluates the performance of Proposed_TAODV in comparison to the current TAODV and Dynamic Source Routing (DSR) protocols. The scope of our research is on analysing essential network performance indicators, such as throughput, end-to-end latency, and packet delivery ratio. We examine these metrics over a range of network scenarios, including different numbers of nodes, data rates, node mobility, and the potential presence of malicious nodes. The Proposed_TAODV exhibits substantial improvements in network efficiency and security, constantly surpassing the performance of current protocols in managing massive volumes of traffic, dynamic network structures, and security risks, as shown by extensive simulations. The improved performance may be due to the protocol's strong routing algorithms and sophisticated trust management system, which efficiently address the problems presented by the dynamic and frequently hostile environment of MANETs. The results of this research highlight the capability of Proposed_TAODV to improve the dependability, safety, and overall performance of MANETs, making it a viable alternative for intricate networking situations where traditional protocols are inadequate.